Pengaruh tugas terhadap kesehatan mahasiswa - Rahman, Humaidi (Maliki Interdisciplinary Journal, 2024)
Health is a state of physical, mental and social well-being that enables all people to be socially and economically productive. Health does not only mean physical or external health, but also mental or emotional health. Health is an important factor in human life, and for lectures to run smoothly, students need good mental health. Student health is related to mental health. Everyone wants to live a healthy life, because they cannot maintain good eating, sleeping and social patterns, and there are no clear boundaries between normal and deviant. Students’ mental health is often underestimated, and experts are trying to develop benchmarks for individual mental health. There is no boundary between mental health and mental disorders. A person is said to be healthy if there is no possibility of special complaints, adaptive orientation, or developmental orientation. Assignments are students’ duties and responsibilities, and assignments are closely related to confusion, forcing them to stay up late and eat late at night.